Evaluating the training programme on ISO 9002 at Esprit Corporation Sdn. Bhd. - Khoo, Guat Tin (1997)
The Malaysian Construction Industry has been beset with a lot of problems of late owing a lack of quality control and safety. The Malaysian Government has called for and promoted an awareness for quality management with the introduction of the ISO 9000 series. Esprit Corporation Sdn. Bhd. is one of the many companies which has taken the challenge of implementing the quality management system of the ISO 9002. The company has opted for a series of training in the ISO 9002 towards the implementation and certification of ISO 9002. The implementation of the ISO 9002 is not without its problems and proper adequate training is the key to eradicating these problems.This study was conducted primarily to evaluate the training programme on ISO 9002 at Esprit Corporation Sdn. Bhd. as perceived by the Managerial Executives through their level of reaction and learning. It was also to evaluate whether the training programme on ISO 9002 at Esprit Corporation Sdn. Bhd. had been successful in ensuring that all the Managerial Executives received the training appropriate to establish the documentation structure for the implementation and maintenance of the ISO 9002 in the company. Finally it attempted to find out the reaction level of the Managerial Executives towards the training programme on ISO 9002 and the learning level of the Managerial Executives in the ISO 9002, the documentation requirement of ISO 9002 and the work procedures in the company through such aspects as knowledge, skills and attitude. A three part interview schedule was developed. It covers the Personal Characteristics of the Managerial Executives, the Reaction level of the Managerial Executives towards the training programme on ISO 9002 and the Learning level of the Managerial Executives which was further subdivided into three sections, namely; Knowledge in the ISO 9002 and the Documentation Requirement in the ISO 9002; Knowledge pertaining to the Skills of Work Procedures in the company; and the Attitudinal level of the Managerial Executives towards the ISO 9002.The results of the statistical analysis revealed that the Managerial Executives reacted positively towards the training programme on 9002, implying that learning will most probable be favourable with better commitment and support for the implementation of the ISO 9002. The learning level also showed satisfactory results.